Manufacturing of an immediate removable partial denture with an intraoral scanner and CAD-CAM technology: a case report - Francois Virard; Laurent Venet; Raphaël Richert; Daniel Pfeffer; Gilbert Viguié; Alexandre Bienfait; Jean-Christophe Farges; Maxime Ducret (BMC, 2018)
Abstract Background Incisor loss constitutes a strong aesthetic and psychologic traumatism for the patient and it remains a challenging situation for the dental practitioner because of the necessity to rapidly replace the lacking tooth. Various therapeutic procedures have been proposed to replace the incisor concerned, for example by using a removable partial denture. However, the manufacturing of such a denture with classical procedures is often subject to processing errors and inaccuracies. The computer-aided design and computer-aided manufacturing (CAD-CAM) technology could represent a good alternative, but it is currently difficult because of the lack of dental softwares able to design easily immediate removable partial dentures. Case presentation A 30-year- patient complained about pain caused by a horizontally and vertically mobile maxillary right central incisor. After all options were presented, extraction of the traumatized incisor was decided due to its very poor prognosis, and the patient selected the realization of a removable denture for economic reasons. The present paper proposes an innovative procedure for immediate removable denture, based on the use of an intraoral scanner, CAD with two different softwares used sequentially, and CAM with a 5-axis machine. Conclusions We show in this report that associating an intraoral scanner and CAD-CAM technology can be extended to immediate dentures manufacturing, which could be a valuable procedure for dental practitioners and laboratories, and also for patients.